1997
DOI: 10.1002/(sici)1099-1166(199702)12:2<183::aid-gps584>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

The Prince Henry Hospital Dementia Caregivers? Training Programme

Abstract: Objective. To describe the theory, elements and practice of a successful caregiver training programme; and report the 8‐year outcome. Design. Prospective, randomized control trial and longitudinal follow‐up over approximately 8 years. Setting. Psychiatry unit, general teaching hospital, Sydney, Australia. Participants. 96 persons less than 80 years old with mild to moderate dementia and their cohabiting caregivers. Interventions. All patients received a 10‐day structured memory retraining and activity programm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
1
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(108 citation statements)
references
References 31 publications
2
104
1
1
Order By: Relevance
“…Brodaty et al 33 carried out a randomised trial comparing a carer training programme (either immediate or waiting list control subjects) with a 10-day respite intervention with no training. The 8-year survival analysis indicated that carer training delayed both death and institutionalisation; the respite intervention, in comparison, although coupled with memory retraining for dementia patients, was associated with a shorter mean time to institutionalisation.…”
Section: Respite As a Predictor Of Institutionalisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Brodaty et al 33 carried out a randomised trial comparing a carer training programme (either immediate or waiting list control subjects) with a 10-day respite intervention with no training. The 8-year survival analysis indicated that carer training delayed both death and institutionalisation; the respite intervention, in comparison, although coupled with memory retraining for dementia patients, was associated with a shorter mean time to institutionalisation.…”
Section: Respite As a Predictor Of Institutionalisationmentioning
confidence: 99%
“…One study reported that, compared with a carer training programme, 33 carers in receipt of respite tended to institutionalise care recipients faster. In contrast, Riordan and Bennett 49 found that respite users tended to keep the care recipient in the community for significantly longer than matched control subjects.…”
Section: Summary: the Impact Of Respite On Care Recipient Institutionmentioning
confidence: 99%
“…33 A range of psychosocial approaches can be offered, primarily targeted at the family. Although the evidence on interventions to support families is mixed, 34 the conclusion from major studies is that a combination of family meetings and peer support is effective in reducing care-giver strain and delaying institutionalization, [35][36][37] and that the best outcomes are achieved by multidimensional interventions individually tailored to carer needs. 38,39 Cognitive rehabilitation-using for example memory aids and training-has been applied with promising results in mild/moderate dementia.…”
Section: Psychosocial Interventionsmentioning
confidence: 99%
“…Many of the recommendations regarding the role of the family physician in supporting dementia caregivers can be subsumed under the three dimensions used by Brodaty et al 11 in designing their comprehensive program: (a) education, (b) psychological support and (c) assistance with social support.…”
Section: The Role Of the Primary Care Physicianmentioning
confidence: 99%